2007
DOI: 10.1017/s0959259808002396
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate prescribing in older people

Abstract: As people age they almost invariably develop diseases which lead to the prescription of drugs – both to prevent disease progression and for symptomatic relief. Unfortunately, drug treatment in later life is also problematic. There is a dearth of evidence on the efficacy of drugs in people over the age of 80, and members of this age group are at highest risk of adverse drug reactions (ADR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…PIM is defined as a medication that should be avoided in older adults due to their considerable risk of adverse reactions and the lack of clinical evidence behind their benefits when safer and more or equally effective therapeutic options are available [ 11 ]. PIM use occurs when the risk associated with the prescribed drugs outweighs potential benefits, especially when effective alternatives are available [ 12 ] whereas, ADEs are considered the fifth most common cause of mortality among hospitalised patients [ 13 , 14 ]. Several studies reported the cause of most ADEs as PIM, which are common in ambulatory care [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PIM is defined as a medication that should be avoided in older adults due to their considerable risk of adverse reactions and the lack of clinical evidence behind their benefits when safer and more or equally effective therapeutic options are available [ 11 ]. PIM use occurs when the risk associated with the prescribed drugs outweighs potential benefits, especially when effective alternatives are available [ 12 ] whereas, ADEs are considered the fifth most common cause of mortality among hospitalised patients [ 13 , 14 ]. Several studies reported the cause of most ADEs as PIM, which are common in ambulatory care [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Since the original paper was written significant developments have occurred, in particular with regard to explicit prescribing criteria and use of information technology. These will be discussed below and the concept of appropriate prescribing in older people and the difficulties in achieving optimal prescribing practice will be explored.…”
Section: Introductionmentioning
confidence: 99%